Analysis of thermo-mechanical behavior for ceramic powder during cold and warm compaction processes / Mohd Sani Jamailudin and Mohamed Azwa Hasshim - Jamailudin, Mohd Sani; Hasshim, Mohamed Azwa (2004)
The thermo-mechanical behavior of alumina ceramic powder during cold and warm compaction processes was studied. The mechanical characterization such as green density, sintered density and linear shrinkage of the sintered compacted alumina ceramic powders were included in the study. The effect of sintering temperature towards the density also was studied. Experimental works were carried out in the laboratory for a simple cylindrical of compacted powder using a uniaxial die compaction machine. The parameters which were measured were force and displacement. This will provide information on the tooling movement and the required force for compaction of powders. The density and linear shrinkage is obtained by measuring the dimensions of the green compacted powder and sintered compacted powder. Two types of powder are used which is pure alumina (NO 115) and alumina with acrylic binders (NM9620). The experimental work results were discussed in order to find the reason for such behavior and characteristic. From the compaction results, compaction at 150°C indicate that less force is needed to compact powder compare to compaction at room temperature. Both green and sintered density of compaction temperature atl50°C is higher and relatively close to the theoretical density. Linear shrinkage indicates that diameter shrinkage will increase as the sintering temperature increases for both powders. For powders compacted at room temperature, the height shrinkage will increase as the sintering temperature increased but for powders compacted at 150°C, the height shrinkage will decrease as the sintering temperature increased.